Techno-economic Comparative Analysis of Floating/On-Ground Solar PV System for Electrification of Gilgel Gibe I Auxiliary Load in Ethiopia - Mekonnen, Tefera; Ramayya, Venkata; Bhandari, Ramchandra; Minaye, Emiyamrew; Tsegay, Shewit (International Journal of Energy Economics and Policy, 2024)
Ethiopia is well endowed with solar energy resources with daily average radiation ranging from 4.5 to 7.5 kWh/m2/day. The significant electricity consumption of the country is reliant on hydropower. This dependence on hydropower makes the country susceptible to weather and climate changes, such as droughts, which can lead to reduced water levels in hydropower reservoir and reduced electricity generation. The application of solar floating photovoltaic (FPV) in the existing hydro reservoir would provide solar electric power to support hydropower generation especially during dry periods, and decrease evaporation losses. This implementation also has the cascading effect of increasing the solar power generation from the PV system by reducing the panel temperature through efficiency gain while saving the land requirement for installing the same PV system. Especially for countries like Ethiopia where agriculture is the key source of economy, optimal usage of land is very important. Thus, in this research, a techno-economic comparative analysis of 4MW Grid-tied FPV and ground-mounted PV system on Gilgel gibe I reservoir in Ethiopia for supplying the auxiliary load of the generation plant is done. The results showed that the proposed FPV system has 6.9% more electricity generating capacity than land-mounted PV system and saves 74,400m3 of water from evaporation annually. The FPV plant will also save the land cost burden, and results the levelized cost of energy (COE) 0.043$/kWh, which is 15.7 % less than land-mounted PV systems. In another way, the proposed FPV system indicated a positive impact on the environment by reducing 993 tons of greenhouse gas emission annually. Thus this research results will offer a clear directions for the concerned stockholders to implement FPV technology on the Ethiopian hydro reservoirs.